Template to Perpetrate: An Update on Violence in Autism Spectrum Disorder. Issue 1 (January 2016) - Im, David S.
Abstract: Introduction: For the past two decades, researchers have been using various approaches to investigate the relationship, if any, between autism spectrum disorder (ASD) and violence. The need to clarify that relationship was reinforced by the tragic mass shooting at Sandy Hook Elementary School in Newtown, Connecticut, in December 2012 by an individual diagnosed with Asperger's syndrome. The purpose of this article is (1) to provide an updated review of the literature on the association between ASD and violence, and (2) to examine implications for treating, and for preventing violence by, individuals with ASD. Method: A review of all published literature regarding ASD and violence from 1943 to 2014 was conducted using electronic and paper searches. Results: Although some case reports have suggested an increased violence risk in individuals with ASD compared to the general population, prevalence studies have provided no conclusive evidence to support this suggestion. Among individuals with ASD, however, generative (e.g., comorbid psychopathology, social-cognition deficits, emotion-regulation problems) and associational (e.g., younger age, Asperger's syndrome diagnosis, repetitive behavior) risk factors have been identified or proposed for violent behavior. Conclusions: While no conclusive evidence indicates that individuals with ASD are more violent than those without ASD, specific generative and associational risk factors may increase violence risk among individuals with ASD. Further research would help to clarify or confirm these findings, suggest potential directions for evaluation, treatment, and prevention, and potentially provide compelling empirical support for forensic testimony regarding defendants with ASD charged with violent crimes.